COMPANY REGULATION DEVELOPMENT ASSISTANCE PT. KARYA PRIMA VALASINDO - Yana Oetary; Winda Fitri (ConCEPt - Conference on Community Engagement Project, 2022)
Employers who employ at least 10 workers/laborers are required to make company regulations. Company regulations are regulations made in writing by employers that contain work requirements and company rules and regulations. It is important to establish company regulations that are in accordance with the law to ensure that workers/laborers can work safely. The method used is empirical methodology, the authors go directly to the field to examine the actual situation in the practical work place and collect the required data and interview several related. After the necessary data is collected, the next stage is to analyze and then implement the project that has been designed by the author. To establish company regulations made by employers, it is necessary to consult with experts and trade unions in the process of establishing regulations. After the company regulations are drafted, workers can work as much as possible in accordance with company regulations and become more aware of labor laws.